The Museums of Geology and Paleontology as Geoeducational Learning Environments for Raising Climate Change Awareness - Kondyli, Christina; Psychogiou, Maria; Hara Drinia (Sustainability, 2024)
Museums are called to respond to contemporary challenges and contribute to the formation of more progressive societies. One of the major challenges of our time is climate change and sustainability, and museums could construct cocreated narratives around climate and implement targeted actions for the audiences through their sensorial and affective experiences. More specifically, Geology and Paleontology museums are repositories of knowledge on geoheritage and geoconservation, recognized for their scientific, pedagogical, cultural, and recreational values. The educational potential of geological and paleontological exhibits could be used in informal education activities regarding the climate emergency and the need for sustainability. Taking the above into consideration, this study focuses on both the creation and the evaluation of an educational program for the Natural History Museum of Arsakeio Campus in Psychicko. According to our findings, students really enjoyed their experience in the Museum, gained knowledge regarding mass extinctions driven by climate change, and suggested ways to tackle the current problems and promote our planet’s sustainability.